Aspect Purchasing Decisions at Consumers Lazada: Trust, Price, Tagline - Dirwan; Orfyanny S.Themba; Fitriani Latief (Jurnal Economic Resource, 2021)
Lazada is one of the most popular e-commerce apps in ASEAN, with the most users in Indonesia; of course, it continues to compete with its rivals in attracting customers to make purchases. The purpose of this research is to look into the impact of trust on purchasing decisions, the impact of price on purchasing decisions, and the impact of the tagline on purchasing decisions—a survey method using a questionnaire. The population consists of Makassar Lazada shoppers. The sample size was 96 people, and the method used was random sampling. Descriptive analysis and multiple regression techniques are used in data analysis. A total of 96 people took part in the survey. Descriptive analysis and multiple regression techniques are used in data analysis. Trust, price, and tagline all influenced positive and significant purchasing decisions, according to the findings